Delay equations: analysis of a model with feedback using topological degree - Amster, Pablo Gustavo (2015)
We prove the existence of at least one positive θ-periodic solution of a system of delay differential equations for models with feedback arising on regulatory mechanisms in which self-regulation is relevant, e.g. in cell physiology.